Shaping Balipay Intentions Through E-Service Quality and Ease of Use - Gede Crisna Wijaya; Ni Luh Putu Widya Sawitri; Ni Putu Dinda Ratna Dewi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The background of this research is presenting literary contributions to digital financial adoption and technology acceptance, and focusing on the practical benefits of enhancing E-Service Quality and Perceived Ease of Use in improving user engagement with Balipay and the objectives of this study is designed to study and analyze the correlation between E-Service Quality, Perceived Ease of Use, and user adoption of Balipay as a digital financial service. Respondents who regularly engage with the service were determined by means of a sampling method. A total of 100 respondents completed a five point Likert scale questionnaire to provide the necessary data for this study. For data analysis both descriptive and inferential techniques were applied, employing software. The result of this study shows a connection exists among E-Service Quality, Perceived Ease of Use and the adoption of Balipay by users. E-Service Quality exerts a statistically insignificant influence on Usage Intention whereas Perceived Ease of Use exhibits a positive and statistically significant affect. Usage Intention notably affects Usage Decision. Serves as a partial mediator for the impacts of E-Service Quality and Perceived Ease of Use suggesting that ease of use and user intention are crucial factors, in Balipay adoption.This study concludes that E-Service Quality has a positive but non-significant effect on user intention and satisfaction, while Perceived Ease of Use significantly influences intention. This indicates that ease of use is the main variable of Balipay adoption. BPD Bali should focus on improving usability and service responsiveness to enhance user experience and sustain engagement.